Answer:
[tex](x-4)^2+(y+1)^2=29[/tex]
Step-by-step explanation:
We want to find a circle whose diameter has the endpoints (6, 4) and (2, -6).
Since this is the diameter, its midpoint will be the center of the circle. Find the midpoint:
[tex]\displaystyle M=\left(\frac{6+2}{2}, \frac{4+(-6)}2}\right)=(4, -1)[/tex]
So, the center of our circle is (4, -1).
Next, to find the radius, we can find the length of the diameter and divide it by half.
Using the distance formula, find the length of the diameter:
[tex]\begin{aligned} d&=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\\\ &=\sqrt{(2-6)^2+(-6-4)^2}\\\\&=\sqrt{(4)^2+(-10)^2}\\\\&=\sqrt{116}\\\\&=2\sqrt{29}\end{aligned}[/tex]
So, the radius will be:
[tex]\displaystyle r=\frac{1}{2}d=\frac{1}{2}\left(2\sqrt{29}\right)=\sqrt{29}[/tex]
The equation for a circle is given by:
[tex]\displaystyle (x-h)^2+(y-k)^2=r^2[/tex]
Substitute:
[tex](x-4)^2+(y+1)^2=29[/tex]